STUDI TINGKAT KERAMAHAN LINGKUNGAN ALAT TANGKAP PURSE SEINE DI PPI PONTAP KOTA PALOPO - Andi Asni; Kasmawati Kasmawati; Hendardi Tri Sugianto (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2022)
Purse Seine is a fishing gear used to catch fish that have a schooling fish. The purpose of this study is 1) Knowing the composition of the type of fishermen's catch using purse seine fishing gear 2) Knowing the level of environmental friendliness of fishermen's purse seine fishing gear at PPI Pontap Palopo City based on the Code of Conduct for Responsible Fisheries (CCRF). This research was conducted for 1 (one) month, namely in June-July 2022. The methods used in this study are primary and secondary methods. Based on the results of the study; 1) The composition of the type of catch on the purse seine fishing gear at PPI Pontap caught 8 types of fish including male bloating (Rastrelliger kanagurta) with a total weight of 20 trips from 22 ships was 15,111.2 kg, Tembang (Sardinella gibbosa) 10,705.82 kg, Kite deles (Decapterus macrosoma) 9,213.43 kg, Skipjack (Katsuwonus pelamis) 822.9 kg, Selar como (Atule mate) 2,008 kg, Yellow selar (Salaroides leptolepis) 4,230.9 kg, Petek (Secutor indicius) 1,823.9 kg and Gutters (Scomberoides tala) 306.5 kg. So the total overall weight for 20 fishing trips reached 44,223 kg. 2) The level of environmental friendliness of purse seine fishing gear at TPI Pontap is included in the category of very environmentally friendly with a total weight value of 29.